Od čutne izkušnje do javnega sporočila: vzgoja z umetnostjo kot orodje komunikacije podnebnih sprememb/krize - Štirn Janota, Petra; Osojnik, Janez; Hazemali, David; Grušovnik, Tomaž; Štirn, Darja (Komuniciranje okoljske krize, 2025)
Today we associate “caring for the world” and “caring for the children and young people” who come into the world with sustainable development, which involves both maintaining a healthy environment and ensuring ways of life that allow all the world's inhabitants to live with dignity, meaning and hope. One of the ways in which we can develop environmental responsibility and promote sensitivity to the world is through art education, which aims to deepen the artistic experience. As an educational tool, art encourages individuals to discover different worldviews, reflect on the subject, reflect on their role in the world, communicate while making personal hardships easier to cope with, as well as arouse a desire for an engaged social response. In this paper we present the theories underpinning the education through the arts model. We will then present a case study of a didactic model of education through the arts that we have implemented in three schools and that incorporates an interdisciplinary approach. We how we can use the artworks created to communicate with the wider public to express and convey our concerns and our response.